Les dépossessions du paysage. Injustices paysagères, clivages locaux et mécanismes d’exclusion dans le géoparc de Sitia (Crète) - Patrick Moquay; Kalliope Pediaditi (Projets de Paysage)
Considering the political dimensions of the landscape and people’s aspiration for democratic landscape management and planning raise the issue of landscape injustices. This article explores this concept, which covers the dimensions of access to the landscape and participation in its planning and management. It proposes a framework for analysing such injustices which is then applied to the Sitia Geopark in Crete. In an action-research project in support of the geopark team, various qualitative methods (interviews with stakeholders, the perspective of schoolchildren, workshops with the inhabitants, etc.) were used to identify landscape injustices. The examination of the perceptions of landscape injustices expressed by the inhabitants allows us to shed new light on polarisation and conflict in a local community. The divide between the supporters and opponents of the massive development projects implemented in the area (renewable energy installations and a tourist complex) is coupled with another fault line, which includes a feeling of being dispossessed of the landscape and concerns these development projects as well as heritage protection measures.